2010
DOI: 10.3390/molecules15042825
|View full text |Cite
|
Sign up to set email alerts
|

µ-Conotoxins as Leads in the Development of New Analgesics

Abstract: Voltage-gated sodium channels (VGSCs) contain a specific binding site for a family of cone shell toxins known as µ-conotoxins. As some VGSCs are involved in pain perception and µ-conotoxins are able to block these channels, µ-conotoxins show considerable potential as analgesics. Recent studies have advanced our understanding of the three-dimensional structures and structure-function relationships of the µ-conotoxins, including their interaction with VGSCs. Truncated peptide analogues of the native toxins have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
63
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(63 citation statements)
references
References 123 publications
0
63
0
Order By: Relevance
“…Norton [48] reported Mu-conotoxins as leads in the development of new analgesics. Voltage-gated sodium channels (VGSCs) contain a specific binding site for a family of cone shell toxins known as mu-conotoxins.…”
Section: Conotoxinsmentioning
confidence: 98%
See 1 more Smart Citation
“…Norton [48] reported Mu-conotoxins as leads in the development of new analgesics. Voltage-gated sodium channels (VGSCs) contain a specific binding site for a family of cone shell toxins known as mu-conotoxins.…”
Section: Conotoxinsmentioning
confidence: 98%
“…In fact, recent studies have demonstrated that there are different families and super-families of conotoxins [43][44][45][46][47][48][49][50]; which may present different pharmacological activities. For instance, the group of Aguilar and Lopez-Vera, et al [43] studied some I-conotoxins in vermivorous species of the West Atlantic.…”
Section: Conotoxinsmentioning
confidence: 99%
“…[18,20] The structure of δ-EVIA was earlier reported and shown to be characterized by a 1:1 cis/trans isomerism of the Leu 12 -Pro 13 peptide bond within loop 2 (residues [11][12][13][14][15][16][17][18][19] of the disulfide-bridged sequence. [21] Both isomers were separately analyzed (PDB ID: 1G1P and 1G1Z) and, in addition, the exclusive occurrence of a trans leucyl-proline bond was demonstrated for the P13A analog, which was also synthesized by the same group.…”
Section: Introductionmentioning
confidence: 94%
“…[11] This relatively simple interaction mechanism and the perspective to develop µ-conotoxins as drugs to suppress neuronal signaling and therefore to be applied as analgesics has fueled research in this direction. [12] Conotoxins of the O-superfamily also contain three disulfide bridges, but they are much more diverse. Besides the already mentioned -conotoxins, which target voltage-gated Ca 2+ channels, this superfamily comprises µO-and δ-conotoxins, both acting on Na V channels.…”
Section: Introductionmentioning
confidence: 99%
“…Much effort has focused on modifying the 16-residue m-conotoxin KIIIA [71]. Wild-type m-conotoxin KIIIA is a potent blocker of Na V 1.2 with an IC 50 of 5 nM, which is 50-100-fold more potent than at Na V 1.7 [54,55].…”
Section: Animal Toxinsmentioning
confidence: 99%